Automation of beam straightness measurement with image processing tools - Ribeiro, A. Fernando (1996)
For measuring the straightness of moving steel beams, a methodology was developed and an inspection machine was built with a set of image processing tools to control it. The method consists in developing a specific software to perform three main tasks: reading the position of the beams in several positions; correlating all those positions monitored by the cameras; and reporting the quality of the beam straightness. Computer vision technology as a non contact measuring device is used by the inspection machine. From the production process the beams roll on a conveyor therefore several video cameras are used to log information not only about the lateral position but also the height of the steel beams. The user can decide the number of cameras and the distance between them. Should one camera fail or be switched off, the measuring system is not affected as long as the system has a minimum of three cameras extracting acceptable points. The system output is the non linearity deviation of the beam, compensating factors for lateral or angular movements in the horizontal measuring plane of the beam and the beam profile. The output is displayed in a computer screen, according to the line method and the least square method.